Anilinopyrimidine Resistance in Botrytis cinerea Is Linked to Mitochondrial Function - Mosbach, Andreas; Edel, Dominique; Farmer, Andrew D.; Widdison, Stephanie; Barchietto, Thierry; Dietrich, Robert A.; Corran, Andy; Scalliet, Gabriel (Frontiers in Microbiology, 2017)
Crop protection anilinopyrimidine (AP) fungicides were introduced more than 20 years ago for the control of a range of diseases caused by ascomycete plant pathogens, and in particular for the control of gray mold caused by Botrytis cinerea. Although early mode of action studies suggested an inhibition of methionine biosynthesis, the molecular target of this class of fungicides was never fully clarified. Despite AP-specific resistance having been described in B. cinerea field isolates and in multiple other targeted species, the underlying resistance mechanisms were unknown. It was therefore expected that the genetic characterization of resistance mechanisms would permit the identification of the molecular target of these fungicides. In order to explore the widest range of possible resistance mechanisms, AP-resistant B. cinerea UV laboratory mutants were generated and the mutations conferring resistance were determined by combining whole-genome sequencing and reverse genetics. Genetic mapping from a cross between a resistant field isolate and a sensitive reference isolate was used in parallel and led to the identification of an additional molecular determinant not found from the characterized UV mutant collection. Together, these two approaches enabled the characterization of an unrivalled diversity of resistance mechanisms. In total, we report the elucidation of resistance-conferring mutations within nine individual genes, two of which are responsible for almost all instances of AP resistance in the field. All identified resistance-conferring genes encode proteins that are involved in mitochondrial processes, suggesting that APs primarily target the mitochondria. The functions of these genes and their possible interactions are discussed in the context of the potential mode of action for this important class of fungicides.